ON THE EFFECTS OF TECHNOLOGY SHOCKS OVER LABOR INPUT AT BUSINESS-CYCLE FREQUENCIES: AN EMPIRICAL NOTE - Magalhães, Matheus Albergaria de; Picchetti, Paulo (Análise Econômica, 2013)
In the last years, there has been a heated debate over the empirical adequacy of Real-Business-Cycle (RBC) models (GALÍ, 1999; CHRISTIANO; EICHENBAUM; VIGFUSSON, 2003; FRANCIS; RAMEY, 2005). In this empirical note, we check the robustness of some of the main results obtained in this strand of the literature. Our contribution is twofold: first, we provide robust results by using different data sources; second, we show that the results related to labor input’s dynamic pattern over business-cycle horizons are sensitive to the way labor input is modelled. The results obtained favor specifications where labor input is modelled as growth rates. These results may help distinguishing the most desirable empirical specifications to be employed over the debate in the future.